Analysis of Organizational Justice, Competence and Work Motivation to Improve the Performance - Andi Wardana, Miko; Yanita; I Wayan Eka Sudarmawan; Teguh Setiawan Wibowo; Hendrik Pandiangan (SAFE-Network, 2023)
This study examined the influence of organizational justice, competence, and work motivation on the performance of Denpasar city government. The results indicated that organizational justice, competence, and work motivation had positive and significant effects on employee performance. When employees perceive fairness and justice within the organization, possess the necessary competencies, and are motivated to excel in their work, it positively impacts their performance. The combined influence of these variables accounted for 60.4% of the variance in employee performance, indicating a relatively strong relationship. Based on the findings, it is recommended that Government Office focus on promoting fairness and justice, developing employee competencies, and sustaining motivation to enhance performance. Implementing policies and practices that ensure fairness, providing training and development opportunities, and fostering a supportive work environment can lead to a productive and satisfied workforce, resulting in improved performance outcomes and better service delivery to the community. However, it is essential to consider other factors that may also influence employee performance but were not included in this study.